Randomised controlled trial of antibiotics in patients with cough and purulent sputum. - Stott, N C (1976)
Two hundred and twelve adults with cough and purulent sputum of up to one week's duration were allocated randomly to treatment with doxycycline or placebo capsules for up to 10 days. Cough, purulent sputum, feeling "off colour," and time off work lasted as long in treatment and control groups, but running nose persisted for a shorter time in the doxycycline group. The number of new episodes of lower respiratory tract infections, vaginal infections, gastrointestinal upsets, and otitis media over the next six months were the same in both groups, but fewer new upper respiratory infections were experienced by the doxycycline-treated patients. There is no consensus among doctors about using antibiotics in patients with cough and purulent sputum, and these results indicate that otherwise healthy people with these symptoms will usually get better without antibiotic treatment.